Correlation of placental thickness with birth weight in singleton pregnancies - Bedi, Mini; Sharma, Hitika; Sandhu, Parvinder Singh; Minhas, Anshula (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The placenta provides the physiologic link between a pregnant woman and the fetus. During pregnancy, the normal placenta increases its thickness at a rate of approximately 1 millimeter per week. The thickness is considered normal throughout the 2nd and 3rd trimester if between 2 and 4 cm. There is a need to identify the fetus failing to reach its growth potential because an early detection of intrauterine growth retardation will be beneficial to obstetric and neonatal care. Methods: After applying inclusion and exclusion criteria, 251 antenatal women from 24-39 weeks gestation were included in the study. After informed written consent, relevant history, examination, abdominal ultrasound was performed noting fetal biometry and placental thickness. The participants were followed until delivery and birth weight noted. Statistical analysis of birth weight (< and >2500 gm) with placental thickness was done. Results: Mean age of the study was 25.88±4.34 years. The mean placental thickness in group A was 3.33±0.92 cm and in group B was 3.38±0.68 cm. Placental thickness showed a positive correlation with fetal weight (r=0.013), however it was not statistically significant. Uncomplicated pregnancy group had mean placental thickness of 3.40±0.70 cm. The difference of mean for placental thickness was statistically significant with respect to medical disorders (p=0.042). Conclusions: Placental thickness does increase with increasing birth weight of the fetus and hence, subnormal or more than normal placental thickness is helpful in signalling important maternal conditions that may be detrimental to the fetus.